Does the over-medicalisation of pregnancy help to improve neonatal outcomes?. (13th November 2019) - Kundisova, L; Nante, N; Cuccaro, C; Mariottini, E; Alaimo, L
Abstract: Introduction: The over-medicalization of pregnancy is frequent, especially in high-income countries and comports unnecessary costs for health systems. In Italy the national health service guarantees access to health care services, but still a lot of pregnant women search for private health care. This study aimed to analyse if the over-medicalization of pregnancy had an impact on neonatal outcomes. Methods: The cross-sectional study was conducted in Siena (Italy), data were extracted from medical records. All women that gave birth between January 2016-May 2018 and were classified as "low/moderate risk" pregnancy were included. Examined variables were: age, number of obstetrics and ultrasound (US) visits (≤9/≥10), timing of the first visit (<12weeks/>12weeks of pregnancy), health facility (public/private), previous spontaneous abortions (SA) or voluntary interruptions of pregnancy (VIP). The outcome variables were preterm birth (PB) and admission in neonatal intensive therapy unit (NITU). Analysis was performed with Stata 12. Results: A total of 2392 women were included; 22% with≥10 obstetrics visits; 19% with≥10 US visits; 87% had the first visit before 12 weeks of pregnancy and 57% were followed by a private healthcare facility. Six percent of babies were born preterm and 11% were admitted in NITU. The PB condition appeared associated with SA (OR:2.4, 95%CI 1.6-3.6 p < 0.001) and VIP (OR:1.8, 95%CI 1.2-2.8 p < 0.005). Admission in NITU was associated with previous VIP (OR:1.4, 95%CI 1.01-2.03 p < 0.05) and PB (OR:2.16 95%CI 1.37-3.41 p = 0.001). Multiple logistic regression identified only PB as associated with this outcome. Conclusions: Neonatal outcomes do not show association with number of obstetric/US visits and the type of health facility. It seems that controlled pregnancy does not help to reduce the risk of adverse events as premature birth or admission in intensive therapy. Key messages: The over-medicalization of pregnancy is frequent, especially in high-income countries and it has an important impact on health-related costs. More controlled pregnancy does not help to reduce the risk of adverse events as preterm birth and necessity of recovery in neonatal intensive therapy unit.